Gender dimensions of occupational health and safety of street vendors in Kathmandu Valley, Nepal - Shrestha, Abina; Doneys, Philippe; Kusakabe, Kyoko; Perera, L.A.S. Ranjith; Doane, Donna L.; Government of Japan (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
The main goal of this research study is to find out the gender dimensions of occupational health and safety (OHS) among men and women street vendors. The study has highlighted the gendered pattern of health seeking behavior as well as coping mechanism adopted to minimize the OHS problem at both individual and collective level. Using a survey of 300 (176 women and 124 men) respondents street vendors pilot survey, in- depth interviews, focused group discussion (FGD) and observation, the study examined the different OHS issues street vendors experienced through three occupational groups categorized according to different vending items: food group, perishable group and durable group. Findings explore different injuries/diseases/accidents among men and women street vendors which are directly associated with their work environment and types of occupational groups. These suggest external barriers such as low earning, lack of time, educational level and internal barriers i.e. socio-cul tural factors such as social norms and values, gender role in family, patriarchal practices and attitude towards women as determining factors for unequal health seeking behavior between men and women street vendors. Reproductive health problems were found to be higher among women than men, mostly associated with ovul ation cycle (lower stomach pain, over bleeding, etc). Men's reproductive health problems were reflected in the lack of sexual desire. Survey found no sexual harassment among women street vendors. However, harassment in terms of physical assaults, insulting (particularly for male vendors), downsizing vending work, etc were detected resulting in stress, depression and anguish leaving different physical and psychological health impact on men and women street vendors. Finally, the survey found association in their early stage of organizing street vendors and hence lacks the collective bargaining power for their rights. Fu1ihennore, negligible efforts were found in providing OHS protection and were struggling for the management of space for the vendors to vend.
Thesis (M. Sc.) - Asian Institute of Technology, 2011
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Gender and Development Studies, School of Environment, Resources and Development
Keywords: Women -- Employment -- Nepal -- Safety measures; Street vendors -- Nepal